THE PRESENT STATE AND TASKS OF PALEOENTOMOLOGY - Rasnitsyn A.P. (My University, 2003)
The first President's appeal on the occasion of the creation of the International Paleoentomological Society (Krakow, Poland, September 6, 2001).